Charge-reversal polymer nano-modulators for photodynamic immunotherapy of cancer - He, Shasha (2022)
Nanomedicine can regulate the balance between cytotoxic T lymphocytes (CTLs) and suppressive regulatory T lymphocytes (Tregs), which however has been rarely exploited for cancer immunotherapy. We report a charge-reversal polymer nano-modulator (SPDMC N) activated by tumor microenvironment (TME) for photodynamic immunotherapy of cancer. SPDMC N is constructed by conjugating an immunomodulator (demethylcantharidin, DMC) to the side chains of a photodynamic polymer via an acid-liable linker. The negative charge of SPDMC N ensures its high stability in blood circulation and ideal tumor accumulation; exposure to acidic TME reverses its surface charge to positive, enhancing tumor penetration and locally releasing DMC. Upon near-infrared photoirradiation, SPDMC N generates singlet oxygen to ablate tumors and promote maturation of dendritic cells. Released DMC inhibits protein phosphatase 2 (PP2A) activity and decreases Tregs differentiation. Such combinational action induces a sharp increase in CTL/Treg ratio in TME and effectively inhibits both primary and distant tumors in living mice.